3X^2+6x-x-2-20=0 3x^2+5x-22=0 D=25+264=289 x1=-5+17/2*3=12/6=2 X2=-5-17/2*3=-22/6 =-3,667
(а+b)^2= а^2+2ab+d^2.
Представим а , как 2х+5, b как х+6, тогда (корень 2х+5. + корень х+6.)^2=0,
2х+5+2 корень 2х+5. * на корень х+6. +х+6=0;
3х+11+2 корень 2х+5.*на корень х+6.=0;
(3х+11)^2 = (-2корень 2х+5.* на корень х+6)^2;
9х^2 +66х+121= 4(2x+5)(x+6);
9x^2+66x+121-8x^2-68x-44=0;
х^2-2x+77=0;
D=4-4*77=4-308,D<0
нет решения
2¹⁶-2¹⁵=2¹⁵(2-1)=2¹⁵
2¹⁵-2¹⁴=2¹⁴(2-1)=2¹⁴
2¹⁴=2¹³=2¹³(2-1)=2¹³
.............................
2³-2²=2²(2-1)=2²
2²-2¹=2¹(2-1)=2¹
2¹-1=1